Characterization of muscle mass, strength and mobility of critically ill patients with SARS-CoV-2 pneumonia: Distribution by sex, age, days on mechanical ventilation, and muscle weakness - Silva-Gutiérrez, Alexis; Artigas-Arias, Macarena; Alegría-Molina, Andrea; Guerra-Vega, Pablo; Navarrete, Pablo; Venegas, Ángela; Montecinos, Carlos; Vásquez, Lorena; Moraga, Karen; Rubilar, César; Villagrán, Germán; Parada, Rodrigo; et al. (Frontiers in Physiology, 2023)
Objective: Quantify and categorize by sex, age and time spent on mechanical ventilation (MV), the decline in skeletal muscle, strength and mobility in critically ill patients infected with SARS-CoV-2 and requiring MV while at intensive care unit (ICU). Design: Prospective observational study including participants recruited between June 2020 and February 2021 at Hospital Clínico Herminda Martin (HCHM), Chillán, Chile. The thickness of the quadriceps muscle was evaluated by ultrasonography (US) at ICU admission and awakening. Muscle strength and mobility were assessed, respectively, through the Medical Research Council Sum Score (MRC-SS) and the Functional Status Score for the Intensive Care Unit Scale (FSS-ICU) both at awakening and at ICU discharge. Results were categorized by sex (female or male), age (< 60 years old or 60 years old) and time spent on MV (≤10 days or 10 days) Setting: ICU in a public hospital. Participants: 132 participants aged 18 years old or above (women n=49, 60±13 years; men n=85, 59±12 years) admitted to ICU with a confirmed diagnosis of severe SARS-CoV-2 and requiring MV for more than 48 hours were included in the study. Patients with previous physical and or cognitive disorders were excluded. Interventions: Not applicable. Results: Muscle thickness have significantly decreased during ICU stay, vastus intermedius (-11%; P=0.025), rectus femoris (-20%; P<0.001) and total quadriceps (-16%; P<0.001). Muscle strength and mobility were improved at ICU discharge when compared with measurements at awakening in ICU (time effect, P<0.001). Patients 60 years old or on MV for >10 days presented greater muscle loss, alongside with lower muscle strength and mobility. Conclusion: Critically ill patients infected with SARS-CoV-2 and requiring MV presented decreased muscle mass, strength, and mobility during their ICU. Factors associated with muscle mass, such as age >60 years and >10 days of VM, exacerbated the critical condition and impaired recovery.